2000
DOI: 10.1027//1015-5759.16.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report. Applicability of the Dyadic Adjustment Scale for Measurement of Marital Quality with Turkish Couples

Abstract: Summary: The study investigates the reliability and validity of the Turkish Dyadic Adjustment Scale (DAS). Scores of the DAS were studied for its reliability and validity. The sample consisted of 264 married individuals. The α coefficient for the DAS was .92. Computed split-half reliability coefficient was .86. The DAS correlated .82 with the Locke-Wallace Marital Adjustment Test. The original factor structure of the DAS was replicated in the present study. In general, the data indicated that the DAS provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(14 citation statements)
references
References 15 publications
0
9
0
5
Order By: Relevance
“…Participants’ reports of marital quality were measured using the Persian version of Dyadic Adjustment Scale (Sanai Zakir, 2000; DAS; Spanier, 2001). The DAS includes 32 items used to assess partners’ marital quality (e.g., Fişiloǧlu and Demir, 2000; Chiara et al, 2014; Bachem et al, 2018). Twenty-seven items are rated on a 6- point Likert scale (15 items: 0 = always disagree to 5 = always agree ; 12 items 0 = never to 5 = all the time ); two items are on a 5-point Likert scale (0 = never to 4 = everyday ); two items are yes/no type questions (0 = no 1 = yes ); and one is on a 7-point Likert scale (0 = extremely unhappy to 7 = perfect ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants’ reports of marital quality were measured using the Persian version of Dyadic Adjustment Scale (Sanai Zakir, 2000; DAS; Spanier, 2001). The DAS includes 32 items used to assess partners’ marital quality (e.g., Fişiloǧlu and Demir, 2000; Chiara et al, 2014; Bachem et al, 2018). Twenty-seven items are rated on a 6- point Likert scale (15 items: 0 = always disagree to 5 = always agree ; 12 items 0 = never to 5 = all the time ); two items are on a 5-point Likert scale (0 = never to 4 = everyday ); two items are yes/no type questions (0 = no 1 = yes ); and one is on a 7-point Likert scale (0 = extremely unhappy to 7 = perfect ).…”
Section: Methodsmentioning
confidence: 99%
“…Çift Uyum Ölçeği (ÇUÖ): Spanier tarafından 1976 yılında geliştirilen "Çift Uyum Ölçeği (ÇUÖ)", 2000 yılında Fışıloğlu ve Demir tarafından Türkçe'ye uyarlanmıştır (14,15). Toplam 32 sorudan oluşan ölçek likert tipindedir.…”
Section: Veri Toplama Araçlarıunclassified
“…Higher scores indicate an increase in relationship quality. The Turkish version of the scale was created by Fışıloğlu and Demir [22]; its Cronbach’s alpha internal consistency coefficient was 0.92, the split-half reliability coefficient was 0.86, and the correlation with the Marital Adjustment Scale by Locke and Wallace [13] was 0.82. In this study, Cronbach’s alpha was found to be 0.93.…”
Section: Studymentioning
confidence: 99%